Self-driving car with Artificial Intelligence (AI) technology / Asrul Amin Mohd Isa ... [et al.] - Mohd Isa, Asrul Amin; Hasnan, Aimuni Aina; Hashim, Zuyyin; Othman, Jamal (Unit Penerbitan JSKM, 2023)
The autonomous vehicle technology is highly developed and ready for commercial deployment. The self-driving car is a type of autonomous vehicle that can drive autonomously based on Artificial Intelligence (AI). It is based on the use of sensors, actuators, sophisticated algorithms, machine learning systems, and robust processors. The software that autonomous vehicles use to operate is executed by sensors and actuators. Artificial Intelligence (AI) is crucial in operating the autonomous car systems. The National Automotive Policy 2020 (NAP 2020) aims to grow Malaysia’s automotive sector through research and development of new technologies, especially in the fields of Next-Generation Vehicles (NxGV), Industrial Revolution 4.0 (IR 4.0), and Mobility-as-a-Service (MaaS). In this paper, we will focus on the application of AI in autonomous car system. We will also discuss the development of autonomous vehicles.